Pengaruh Model Pembelajaran Penemuan Terbimbing Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 23 Padang - NURFAJRI HAYATI (Departemen Matematika, 2019)
Mathematical concept understanding is one of the goals of mathematic learning must be owned by student. But learning activities is not optimal in facilitating student to improve mathematical concept understanding, so result of test show that mathematical concept understanding of student at SMPN 23 Padang are still low. One of effort to overcome this problem is to apply guided discovery model. The purpose of research is to describe development of mathematical concept understanding of student who learn by using guided discovery model and compare whether mathematical concept understanding of student who learn by using guided discovery model is more better than student who learn by using conventional learning. This type of research is quasy experiment with static group design. The result of research show that mathematical concept understanding of student who learn by using guided discovery model has improve. Then, based on the result of hypothesis test is got that mathematical concept understanding of student who learn by using guided discovery model is more better than student who learn by using conventional learning. So it can be concluded that guided discovery model give influence for mathematical concept understanding.Keywords – Guided Discovery Model, Mathematical Concept Understanding.